Chapter Introduction Moving Memories of Stalin- Era Repression and Displacement - Saramo, Samira (Taylor & Francis, 2023)
The introductory chapter situates the collection within the field of memory studies and the study of Soviet repression and its remembrance. After briefly providing the broad historical context that connects the diverse studies explored by the chapters included in the book, the Introduction reflects on the commemoration of Soviet repression and communism within different memory cultures and the development of memory studies as an academic field. We argue that by bridging case studies of different moments and places under Stalinism, we are able to explore the connections, overlaps, and intersections of how Soviet repression and forced migration has and continues to mark and shape memory, identity, and history. Through an introduction of the twelve chapters of the book, we demonstrate the collection's contribution to better understanding the transnationalism and mobility of memory, the transgenerational aspects of the remembrance of difficult pasts, as well as their implications on the sense of belonging and identification. The chapter highlights that multiply moving - as in mobile, fluid, and emotive - memories not only reflect Eastern European or even European memory culture but reach far beyond.